Konsep Makrifat dalam Kitab Syarḥ al-Ḥikam Karya Kyai Sholeh Darat - Munandar, Siswoyo Aris; Mursalat, Mursalat (TAJDID, 2021)
Makrifat is very important to be known and owned by every Muslim, although generally Sufis view makrifat to be understood and owned by people who have a high station. Therefore, many ordinary people avoid trying to understand makrifat. This study attempts to explain the concept of makrifat in the book Syar al-Ḥikam by Kyai Sholeh Darat. The results showed that Kyai Sholeh Darat's concept of makrifat is the state of a servant who always remembers God and needs Him in any circumstances. The concept of makrifat can cross between groups so that it can be understood in the current conditions. A person who is wise today always remembers Allah and needs Him, so that he can take goodness in everything he faces, both in the fields of technology, social relations, culture, economy, and politics.